Radical hysterectomy + laparoscopic pelvic lymphadenectomy - Molina, Ernesto (2015)
In this publication we present the three interventions laparoscopic radical hysterectomy lymphadenectomy performed by our team in the Hospital III IPSS and the "Ortega" Clinic of the city of Huancayo, which includes the first endoscopic surgery of this type in Peru, held in March 1996.